ADHD, Mental Health and Smart Devices - Exploring Preferences and Perceptions of Smart Watches and Devices and their Potential Role in Supporting Adults with ADHD - Salomonsson Stridsberg, Evelina (My University, 2024)
This thesis explores the potential of wearable technology, specifically smartwatches, to assist individuals with Attention-Deficit/Hyperactivity Disorder (ADHD) in managing daily challenges. ADHD is characterised by inattention, hyperactivity and impulsivity, which can significantly affect executive functioning and overall well-being. The study investigated how individuals with ADHD currently use wearables and other technologies, their preferences, challenges and perceived benefits. It also explored how smartwatches can be tailored to provide support and how these devices can integrate the strategies that individuals with ADHD use to address their everyday challenges. It concludes that smartwatches can be tailored to address these challenges through features like customisable notifications, alarms, timers and reminders that align with the individuals routines, as well as quick note-taking through voice recording. Additionally, it emphasises the importance of providing education, trial opportunities and personalised setup assistance to enhance the adaption and effective use of wearable technology. The findings highlight the need for further research and integration of these tools within healthcare systems or educational institutions to provide additional support for people with ADHD in their daily lives.
Keywords: ADHD; HCI; Mental Health; Smart Devices; Smartphone; Smartwatch; Features; Recommendations